Zollinger-Ellison syndrome Gastrinoma of the pancreas - Campos Pierri, Néstor C.; Revetria, Ricardo; Mazzulla, Fernando; Mascari, José Luis; Andrade, Eduardo; Mañana, Graciela; Verccelli, Jorge (Cirugía del Uruguay, 1986)
Description of a case of Zollinger-Ellison syndrome caused by gastrinoma within the substance of the pancreas, where total gastrectomy and excision of the tumor were performed. Comments on this subject, with bibliographic reference on the diagnosis, treatment and classification within the pathology of this affection.